2015
DOI: 10.1128/aac.02770-14
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Susceptibility among Clinical Nocardia Species Identified by Multilocus Sequence Analysis

Abstract: Antimicrobial susceptibility patterns of 112 clinical isolates, 28 type strains, and 9 reference strains of Nocardia were determined using the Sensititre Rapmyco microdilution panel (Thermo Fisher, Inc.). Isolates were identified by highly discriminatory multilocus sequence analysis and were chosen to represent the diversity of species recovered from clinical specimens in Ontario, Canada. Susceptibility to the most commonly used drug, trimethoprim-sulfamethoxazole, was observed in 97% of isolates. Linezolid an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

12
58
1
9

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(80 citation statements)
references
References 20 publications
12
58
1
9
Order By: Relevance
“…It is important to note that the CLSI recommends broth microdilution to test Nocardia resistance, whereas in this study we used a disc diffusion assay and applied breakpoints from Staphylococci . However, our results are supported by other studies that have found little in vitro resistance to amikacin when using broth microdilution 32 33. Because amikacin seems to have similar efficacy as the other aminoglycosides for non- Nocardia infections and superior efficacy for Nocardia corneal ulcers and because of the relatively high proportion of Nocardia corneal ulcers in South India, amikacin would be a good choice for empiric aminoglycoside therapy in this location.…”
Section: Discussionsupporting
confidence: 85%
“…It is important to note that the CLSI recommends broth microdilution to test Nocardia resistance, whereas in this study we used a disc diffusion assay and applied breakpoints from Staphylococci . However, our results are supported by other studies that have found little in vitro resistance to amikacin when using broth microdilution 32 33. Because amikacin seems to have similar efficacy as the other aminoglycosides for non- Nocardia infections and superior efficacy for Nocardia corneal ulcers and because of the relatively high proportion of Nocardia corneal ulcers in South India, amikacin would be a good choice for empiric aminoglycoside therapy in this location.…”
Section: Discussionsupporting
confidence: 85%
“…McTaggart et al recently reported that some Nocardia spp. such as N. nova, N. farcinica and N. cyriacigeorgica are generally susceptible to imipenem, while other strains such as N. brasiliensis, N. otitidiscaviarum and N. abscessus are not (11). N. concava tends to be resistant to imipenem and cephalosporin from the previous reported cases and our case, so these antibiotics should not be used as a first-line treatment.…”
Section: Discussionmentioning
confidence: 43%
“…Other drugs with broad activity against Nocardia species include imipenem, amikacin and linezolid 20 21. However, antimicrobial susceptibility patterns differ widely among Nocardia species 10 22.…”
Section: Discussionmentioning
confidence: 99%